Book review: Global Portuguese â€“ Linguistic Ideologies in Late Modernity by Luiz Moita-Lopes - Guissemo, Manuel (Multilingual Margins: A journal of multilingualism from the periphery, 2017)
This book has ten articles that emphasize the power of Portuguese language spoken in four continents: Africa, Asia, America and Europe. Apart from these ten articles, the book has an introduction and end with an afterword. The introduction written by Moita-Lopes defends that linguistic ideologies have important roll in construction of actual Portuguese and he argues that â€œin todayâ€™s postcolonial world, it is no longer possible to continue to use theoretical frameworks and analytical tools in the study of Portuguese which are typical of colonial modernity. The contemporary world has been reshaped by globalization processes which have deeply affected and diversified our lives in cultural, social, economic and political terms, configuring what Vertovec (2007) has called superdiversityâ€ (p. 10). This idea of linguistic ideology flows in almost all articles of this book and sometimes it is analysed together with aspects of language policy and globalization.